Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

let f(x)=3x+4 and g(x)=2x-5 find (f-g)(x)

Sagot :

Step-by-step explanation:

find; (f-g)(x)

(f(x) - g(x))

f(x) = 3x + 4, g(x) = 2x - 5

3x + 4 - 2x + 5

x +9